Oxidative Damage and Antioxidant Defense in Ferroptosis - Kuang, Feimei; Liu, Jiao; Tang, Daolin; Kang, Rui (Frontiers in Cell and Developmental Biology, 2020)
Many new types of regulated cell death have been recently implicated in human health and disease. These regulated cell deaths have different morphological, genetic, biochemical, and functional hallmarks. Ferroptosis was originally described as a carcinogenic RAS-dependent non-apoptotic cell death, and is now defined as a type of regulated necrosis characterized by iron accumulation, lipid peroxidation, and the release of damage-associated molecular patterns (DAMPs). Multiple oxidative and antioxidant systems, acting together autophagy machinery, shape the process of lipid peroxidation during ferroptosis. In particular, the production of reactive oxygen species (ROS) that depends on the activity of NADPH oxidases (NOXs) and the mitochondrial respiratory chain promotes lipid peroxidation by lipoxygenase (ALOX) or cytochrome P450 reductase (POR). In contrast, the glutathione (GSH), coenzyme Q10 (CoQ10), and tetrahydrobiopterin (BH4) system limits oxidative damage during ferroptosis. These antioxidant processes are further transcriptionally regulated by nuclear factor, erythroid 2-like 2 (NFE2L2/NRF2), whereas membrane repair during ferroptotic damage requires the activation of endosomal sorting complexes required for transport (ESCRT)-III. A further understanding of the process and function of ferroptosis may provide precise treatment strategies for disease.